Model For Measuring Customer Satisfaction And Delight In Restaurant Industry - Juliana, Juliana; Antonio, Ferdi; Pramezwary, Amelda; Situmorang, Jimmy Muller Hasoloan; Djakasaputra, Arifin; Pramono, Rudy (Politeknik APP Jakarta, 2023)
The purpose of the study was to analyze the effect of brand value, brand credibility, arousal, brand love, online buying on delight and the effect of delight on intention to book a restaurant. The population of this study were restaurant customers in Indonesia, with the sample of 250 respondents collected by online questionnaires using nonprobability sampling technique with convenience sampling—data analysis run by PLS-SEM. Overall, the results of this study are descriptive statistical analysis. This study also offers other areas that deserve more research from the perspective of practitioners and researchers. The results showed that Arousal, Brand Credibility, Brand Love, Brand Value had a positive effect on Intention to Bookrestaurants through the variable of Delight. In contrast, online purchases have no effect on Delight or the hypothesis is not supported because customers feel doubtful and dissatisfied with online purchasing services and still feel afraid due to the occurrence of many frauds in online purchases.